2021
DOI: 10.1155/2021/6674264
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neck and Shoulder Pain on Health-Related Quality of Life in a Middle-Aged Community-Living Population

Abstract: Purpose. Neck and shoulder pain (NSP) is very common in the general population. However, scarce information exists on the relationship between NSP and health-related quality of life (HRQOL) outcomes in this population. The present study described NSP prevalence and its impact on the HRQOL of middle-aged and older persons undergoing a routine medical checkup. Methods. This study recruited 318 subjects (125 males and 193 females; average age, 63.4 years) in good health, collected underwent anthropometric measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…NSP was associated with pain in the upper extremities and lower EuroQol scores, but not with pain in the lower extremities or medical complications 11 . The previous study reported that NSP (+) status was directly related poor HRQOL, and NSP is a predictor of suboptimal physical and mental QOL 37 . However, there has been no analysis of the relationship between NSP and NeP as potential risk factors for decreased QOL in the healthy general population 38 .…”
Section: Discussionmentioning
confidence: 96%
“…NSP was associated with pain in the upper extremities and lower EuroQol scores, but not with pain in the lower extremities or medical complications 11 . The previous study reported that NSP (+) status was directly related poor HRQOL, and NSP is a predictor of suboptimal physical and mental QOL 37 . However, there has been no analysis of the relationship between NSP and NeP as potential risk factors for decreased QOL in the healthy general population 38 .…”
Section: Discussionmentioning
confidence: 96%
“…Neck pain (NP), one of the most common musculoskeletal diseases, exercises a great influence on the daily life of individuals, especially the elderly ( 1 3 ). NP usually refers to pain between the neckline and the spinous process of the first thoracic vertebra ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neck pain is one of the important diseases affecting the quality of life of middle-aged and elderly people, which has brought great social and economic burden to the world and has become a global public health problem [ 1 , 2 ]. Therefore, it is urgent to increase the understanding of neck pain.…”
Section: Introductionmentioning
confidence: 99%